Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Prestasi Kerja Pegawai di Kantor Pelayanan Pajak Pratama Tasikmalaya - Irsan Deriski; Depy Muhamad Pauzy; Dudu Risana (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine the simultaneous and partial effect of work environment and work discipline on employee performance at the tasikmalaya pratama tax service office. The research method used is quantitative method with a survey approach. The sampling technique used a saturated sample with a total sample of 55 people. The data collection technique uses an offline questionnaire. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 25. The results of the study show that work environment and work discipline simultaneously have a significant effect on work performance. Partially work environment has a significant effect on work performance. Partially, the work discipline has a significant effect on work performance.